Generalized finite-element algorithm for laterally loaded piles in permafrost in comparison with measurements - Foriero, A.; Ladanyi, B. (Canadian Geotechnical Journal, 1991)
This paper introduces an elasto-viscoplastic approach for the problem of a single laterally loaded pile in permafrost. The method requires the knowledge of a subgrade modulus k, a creep modulus k r , a yield strength q y , a displacement hardening parameter H* (for an ice-rich soil this amounts to a pure creep problem, thus q y and H* are reduced to zero), and creep parameters n, b, and γ. Finally, the validity of the proposed method is checked against the results of model pile tests that have been carried out at the Northern Engineering Centre of École Polytechnique. Key words: pile, lateral load, laboratory testing, elasto-viscoplastic soil, transient creep law.